A280 RECOVERY OF PROBIOTIC LACTOBACILLI ADMINISTERED SINCE PREGNANCY IN TWO-MONTH-OLD CD-1 MICE OFFSPRING. (1st March 2018) - Stinson, S E; Taibi, A; Henry, K; Sherman, P M; Comelli, E
Abstract: Background: Probiotic administration during pregnancy and lactation may be a strategy to support the establishment of a health-compatible gut microbiome. Temporary increases in Lactobacillus levels in infant fecal samples have been attributed to administration of probiotics during late gestation and breastfeeding. However, the effects of probiotic exposure since conception on the fecal recovery of probiotics during adulthood are unknown. Lacidofil® is a probiotic mixture of Lactobacillus rhamnosus R0011 and L. helveticus R0052, with eubiotic effects in pediatric populations. Aims: The aim of this study was to assess the effect of maternal versus continuous exposure to Lacidofil® strains on probiotic recovery during young adulthood. Methods: 6-8-week-old female, specific pathogen free CD-1 mice were randomized to two groups and started receiving 10 9 CFU/mL Lacidofil® in drinking water (probiotic, P) or water alone (control, C) daily one week prior to mating; treatment continued during pregnancy and lactation. At weaning, dams were sacrificed and the offspring continued their respective mother's treatment (PP or CC) or were switched (PC or CP) (n = 6–9/sex/group). Fecal DNA was extracted at weaning and two months of age. Lacidofil® strains were quantified by q-PCR. Results: Probiotic administration did not affect dams and pups body weights nor litter sizes. At weaning, strains R0011 and R0052 were detected in the feces of both dams and offspring receiving probiotics, but not in controls. In the PP study group, probiotic strains increased from weaning to two months of age, but were undetectable in two-month-old PC and CC mice. There were both maternal and pup treatment effects on fecal counts of both probiotic strains in males (R0011: dam diet, P = 0.011; pup diet, P = 0.000; R0052: dam diet, P = 0.007; pup diet, P = 0.000) and females (R0011 dam diet, P = 0.040; pup diet, P = 0.000; R0052: dam diet, P = 0.043; pup diet, P = 0.000) at two months of age. Conclusions: Fecal amounts of Lacidofil® strains increase with duration of administration and depends on in utero exposure. Administration of Lacidofil® post-weaning, does not achieve the same bacterial colonization of the gut compared to exposure since conception. Probiotics have the potential for programming the developing gut microbiome. These novel obervations could have implications for dietary guidelines targeting pregnant and lactating mothers. Funding Agencies: NSERC to EC, CIHR to PMS, OGS and NSERC CGSM to SES, Lallemand Health Solutions & Lawson Family Chair in Microbiome Nutrition Research to EC.